Diagnostic value of spinal US: comparative study with MR imaging in pediatric patients - Rohrschneider, Wiltrud; Forsting, Michael; Kassa Darge; Tröger, Jochen (Radiology, 1996)
PURPOSE: To assess the diagnostic value of spinal ultrasonography (US) in pediatric patients. MATERIALS AND METHODS: The findings on 38 spinal US scans in 30 patients (mean age, 5.5 months) were compared with those of corresponding magnetic resonance (MR) images. RESULTS: MR imaging showed a normal spinal canal in 14 of 38 examinations, a congenital anomaly in 22, and a neoplasm in two. In 32 of 38 examinations, US allowed exactly the same diagnosis as MR imaging. In five examinations, US depicted the main abnormality, but MR imaging revealed additional findings. In one examination, no consensus was achieved. Whenever US scans were normal, MR images also did not depict any spinal disorder. In all 24 examinations with abnormal MR findings, US enabled detection of the abnormality. CONCLUSION: Spinal US seems to represent a valuable diagnostic tool for congenital anomalies of the lower spine in infants and is recommended as the primary imaging modality in those patients.